Rayleigh waves in an incompressible orthotropic half-space coated by a thin elastic layer - Vinh, P.C.; Linh, N.T.K.; Anh, V.T.N. (Archives of Mechanics, 2014)
The present paper is concerned with the propagation of Rayleigh waves in an orthotropic elastic half-space coated with a thin orthotropic elastic layer. The halfspace and the layer are both incompressible and they are in welded contact to each other. The main purpose of the paper is to establish an approximate secular equation of the wave. By using the effective boundary condition method an approximate secular equation of third-order in terms of the dimensionless thickness of the layer is derived. It is shown that this approximate secular equation has high accuracy. From it an approximate formula of third-order for the velocity of Rayleigh waves is obtained and it is a good approximation. The obtained approximate secular equation and formula for the velocity will be useful in practical applications.